2006
DOI: 10.1590/s0036-46652006000400003
|View full text |Cite
|
Sign up to set email alerts
|

Mass treatment for intestinal helminthisis control in an Amazonian endemic area in Brazil

Abstract: SUMMARYThe objective of the present study was to estimate the prevalence of soil-transmitted helminthiasis and evaluate the sanitary conditions and the role of a mass treatment campaign for control of these infections in Santa Isabel do Rio Negro. A crosssectional survey was carried out in 2002, to obtain data related to the sanitary conditions of the population and fecal samples for parasitological examination in It was also noticed a decrease of prevalence of infection by Entamoeba histolytica / dispar (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 23 publications
1
6
0
6
Order By: Relevance
“…We found that the social status of the individuals as well as housing conditions and level of hygiene are closely related to the test results. Data from literature show that the combination of measures such as sanitation and health education is the method of choice for reducing parasitic infections 3 . Indeed, a recent study 2 using advanced statistical modeling to control individual and ecological potential confounders, demonstrated the impact on intestinal parasites of sanitation improvements implemented on a large population scale.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the social status of the individuals as well as housing conditions and level of hygiene are closely related to the test results. Data from literature show that the combination of measures such as sanitation and health education is the method of choice for reducing parasitic infections 3 . Indeed, a recent study 2 using advanced statistical modeling to control individual and ecological potential confounders, demonstrated the impact on intestinal parasites of sanitation improvements implemented on a large population scale.…”
Section: Discussionmentioning
confidence: 99%
“…6 For both Giardia and E. histolytica, stool antigen tests or PCR-based tests are more sensitive and accurate than stool microscopy. [31][32][33] Whether to replace stool O&P examinations with antigen testing for all refugees, only in those with symptoms, or only in children, needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…These concerns, together with a need to better understand a number of fundamental clinical and epidemiological aspects of human helminth infections as well as their interactions with geographically overlapping coinfections (e.g., malaria and HIV/AIDS) have created an urgency for stepped up clinical research activities as they relate to largescale helminth control. Such activities have focused around three major areas: first, a reexamination of the health impact of human helminthic infections, with particular interest in the effects of mono- and polyparasitism on childhood growth and development as well as their effects on pregnancy and birth outcomes (63,(136)(137)(138)(139)(140); second, large-scale monitoring and evaluation of MDA and integrated control, along with operational research with goals to improve the access of populations to anthelminthic drugs and to monitor for possible drug resistance (141)(142)(143)(144)(145); and third, the development of new tools to control helminth infections, that is, drugs, diagnostics, and vaccines (19,146).…”
Section: Global Control Of Helminthiases and Clinical Research Imperamentioning
confidence: 99%